Merging county administrations – cross-national evidence of fiscal and political effects - Sebastian Blesse; Felix Roesel (Local Government Studies, 2019)
While many central governments amalgamate municipalities, mergers of larger county administrations are rare and hardly explored. In this article, we assess both fiscal and political effects of county mergers in two different institutional settings: counties act autonomously as upper-level local governments (Germany), or counties being decentralised branches of the state government (Austria). We apply difference-in-differences estimations to county merger reforms in each country. In both cases, some counties were amalgamated while others remain untouched. Austrian counties (Bezirke) and German counties (Landkreise) widely differ in terms of autonomy and institutions, but our results are strikingly similar. In both cases, we neither find evidence for cost savings nor for staff reductions. Instead, voter turnout consistently decreases in merged counties, and right-wing populists seem to gain additional support. We conclude that political costs clearly outweigh fiscal null benefits of county merger reforms – independent of the underlying institutional setting.
Keywords: 330; County mergers; local government; expenditures; local elections; voter turnout